Pengenalan Ungkapan Melayu Terhadap Berpikir Teliti dalam Buku Kearifan Melayu Karya Tenas Effendy Pada Siswa SMA Negeri 1 Kampar Kecamatan Kampar Kabupaten Kampar - Amanan Amanan; Hermansyah Hermansyah; Juswandi Juswandi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2022)
The introduction of the Malay expression about Think Carefully in the book of wisdom Malay Tenas Effendy, at various levels of the school at present very low, while Thoroughly Thingking Carefully in the past or now is very much needed. If a person does a job less carefully, it can make a job can not be completed well, it can even cause losses. Therefore, we should take lessons from the Malay word about Think Carefully because this is the need for people to know and understand about Thinking Research in Malay expression of Tenas Effendy. The introduction of think carefully to the younger generation, especially students of SMA Negeri 1 Kampar, Kampar District, Kampar Regency is carried out so that they think more carefully so that they can reduce the carelessness that many people have today. Therefore, the introduction of Thinking Carefully in Malay Expressions is important.